Long-Term Follow-Up of Patients With Idiopathic Pulmonary Fibrosis Treated With Pirfenidone or Nintedanib: A Real-Life Comparison Study - Cameli, Paolo; Refini, Rosa Metella; Bergantini, Laura; d’Alessandro, Miriana; Alonzi, Valerio; Magnoni, Carlo; Rottoli, Paola; Sestini, Piersante; Bargagli, Elena (Frontiers in Molecular Biosciences, 2020)
Background. Pirfenidone and nintedanib are the sole pharmacological therapies currently approved for idiopathic pulmonary fibrosis (IPF). Limited comparison data is available in literature, despite they are both prescribed for mild-to-moderate disease. Here, we describe our almost ten-years real-life experience with antifibrotic treatment to investigate potential differences in terms of efficacy. Population and methods. We retrospectively recruited patients diagnosed with IPF and treated with pirfenidone or nintedanib at Siena Referral Centre. Clinical, functional, safety and radiological data was collected at baseline and during the follow-up, according to our Centre protocol. Results. We retrospectively recruited 263 IPF patients (139 treated with pirfenidone and 124 with nintedanib) in the study. After 885.3 ± 559.5 days of observation, the median survival was 1224 days. No significant differences were found between pirfenidone and nintedanib in terms of survival and time to decline of forced vital capacity > 10% (p=0.8786 and p=0.1677, respectively). A smaller lung diffusion for carbon monoxide (DLCO) decrease was found after one year of therapy with nintedanib in respect to pirfenidone (p=0,0167). Overall, 21 patients permanently discontinued antifibrotic treatment due to side effects (14 with pirfenidone, 7 with nintedanib); no fatal adverse events were recorded. Discussion. Our results showed a similar effectiveness between pirfenidone and nintedanib in terms of mortality and functional disease progression. Both drugs confirmed their good tolerability profile and no new safety alerts were observed. Nintedanib was associated with a smaller reduction of DLCO after one year of follow-up compared with pirfenidone, maybe due to its antiangiogenic properties.